2021
DOI: 10.1108/et-04-2021-0121
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation and academic perspectives on authentic assessment for applied business higher education in a top performing Asian economy

Abstract: PurposeThe purpose of authentic assessment can enrich students with a set of skills that can have a significant impact on their employability. The key aim of these actions is to equip students with the practical skills to be work ready. The focus here is to demonstrate effects on student satisfaction and observations from teaching staff accrued over several semesters in an educational institution after introducing authentic assessments.Design/methodology/approachThis paper used a set of scaffolded authentic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The process and the results are summarized in this visual thinking (Figure 1). The use of a rubric to assess competencies for employability becomes a support tool for real assessment and it has been confirmed that this favours the expression of competencies for professional activity (Boud, 2020), as well as the inclusion of different people (Akbari et al, 2022). Having assessment tools in vocational training which are also open, stress-free, adapted to the style of learning of students, as indicated by Ibarra-Sáiz et al (2020), Boud, (2020 and Knight and Drysdale (2020), may make it more likely for graduates to adapt to the emerging economy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The process and the results are summarized in this visual thinking (Figure 1). The use of a rubric to assess competencies for employability becomes a support tool for real assessment and it has been confirmed that this favours the expression of competencies for professional activity (Boud, 2020), as well as the inclusion of different people (Akbari et al, 2022). Having assessment tools in vocational training which are also open, stress-free, adapted to the style of learning of students, as indicated by Ibarra-Sáiz et al (2020), Boud, (2020 and Knight and Drysdale (2020), may make it more likely for graduates to adapt to the emerging economy.…”
Section: Discussionmentioning
confidence: 99%
“…Having assessment tools in vocational training which are also open, stress-free, adapted to the style of learning of students, as indicated by Ibarra-Sáiz et al (2020), Boud, (2020 and Knight and Drysdale (2020), may make it more likely for graduates to adapt to the emerging economy. This is particularly significant in the midst of the volatility which has marked the global economy following the COVID-19 pandemic, as is also highlighted by Mahajan et al, (2022) and Akbari et al (2022). However, the benefits offered by this rubric to assess competencies for employability are not enough to overcome the problems regarding the differences between syllabuses and corporate demands (Senan & Sulphey, 2022;Olo et al, 2022;Mahajan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within higher education, academic staff members with teaching qualifications or training are not the majority, so when they are tasked with improving the student learning experience, there is a need for academic development to enable transformation in assessment design and implementation (Akbari et al, 2021;Maclellan, 2004). According to Sadler and Reimann (2018), research into academics' conceptualisation of assessment indicates it is complex, in part due to the dual purposes of assessment; that is, the requirement for it to be for learning as well as of learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within higher education, academic staff members with teaching qualifications or training are not the majority, so when they are tasked with improving the student learning experience, there is a need for academic development to enable transformation in assessment design and implementation (Akbari et al. , 2021; Maclellan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%